Is binge-watching competing with sleep? And winning? - Jindal, Ripu D. (J Clin Sleep Med, 2020)
Jindal RD. Is binge-watching competing with sleep? And winning? J Clin Sleep Med. 2020;16(suppl_1):31S–32S.